Besoins criants, gains modestes : l'accès à des soins de santé mentale en français en Ontario, 1968–1986 - Arsenault, Mathieu; Martel, Marcel (Besoins criants, gains modestes : l'accès à des soins de santé mentale en français en Ontario, 2017)
Les gains en matière de soins de santé mentale en français arrivent au compte-goutte entre 1968 et 1986. L'État ontarien agit avec prudence dans ce dossier. Malgré les pressions des individus et de l'Association canadienne-française de l'Ontario, la mise en place de soins de santé mentale en français s'est butée à de nombreux obstacles tels que la pénurie de personnel parlant français, les difficultés à attirer ce personnel et à les inciter à demeurer notamment dans le Nord, les carences du système d'éducation à former des francophones, les hésitations du gouvernement ontarien, mais aussi l'hostilité au fait français.

Compétences linguistiques et culturelles des organisations de santé. Analyse critique de la littérature - Aucoin, Léonard (InfoVeille Santé, 2008)

Special report on French language health services planning in Ontario, 2009 - Boileau, François (Office of the French Language Services Commissioner, 2009)

La santé en contexte francophone minoritaire au Canada : 20 ans de recherche: Introduction - Bouchard, Louise; Savard, Jacinthe; Dumond, Morgan (Minorités linguistiques et société, 2024)

Acculturation, vitality, and bilingual healthcare - Bourhis, Richard Y.; Montreuil, Annie (The Oxford handbook of acculturation and health, 2017)
Chapter: 4

Barrières linguistiques dans l'accès aux soins de santé - Bowen, Sarah (Santé Canada, 2001)

Impact des barrières linguistiques sur la sécurité des patients et la qualité des soins. Rapport final - Bowen, Sarah (Société Santé en français, 2015)

Language barriers in access to health care - Bowen, Sarah (Health Canada, 2001)

The impact of language barriers on patient safety and quality of care. Final report - Bowen, Sarah (Société Santé en français, 2015)

La formation des professionnels de la santé au Nouveau-Brunswick ou l'application du principe de I'inégalité - Braën, André (Administration publique du Canada, 2008)
Sommaire: Comme partout ailleurs au Canada, le régime des soins médicaux et hospitaliers du Nouveau-Brunswick est universel. Les services de santé qui sont ainsi offerts à la population sont fournis sur une base individuelle, sans égard à la race ou à la langue de l'individu. D'autre part, le Nouveau-Brunswick est la seule province canadienne qui a proclamé officiellement l'egalité juridique des deux communautés linguistiques qui la composent. Dans un tel contexte, l'assurance de la disponibilité de services de santé dans sa propre langue devient un principe général important; elle affecte directement la qualité des services fournis à la minorité francophone de cette province ainsi que le développement de ses institutions hospitalières. L'auteur cherche ici a analyser si, au-delà de cette dialectique juridique dont semble friand le Nouveau-Brunswick, l'égalité de fait est recherchée dans le secteur de la formation des spécialistes de la santé. Puisque cette formation est extrêmement onéreuse et étant donné le nombre restreint de ses habitants, le Nouveau-Brunswick a conclu plusieurs accords avec des provinces voisines dans le but de permettre à ses étudiants de s'inscrire dans des programmes de sciences de la santé non disponibles dans la province. Ayant choisi l'angle linguistique, l'auteur examine les structures mises en place pour appliquer ces accords, le nombre et la qualité linguistique des étudiants ainsi que les sommes dépensées par le Nouveau-Brunswick dans le cadre de l'application de ces ententes. Finalement, il mesure l'intensité de l'effort que fournit cette province pour former des spécialistes francophones.

Évaluation de la validité des preuves présentées dans l’étude intitulée "Language Barriers in Health Care Settings: An Annotated Bibliography of the Research Literature" - Bureau d'appui aux communautés de langue officielle (Santé Canda, 2008)

Vivre et travailler en français à Iqaluit (Nunavut) : regards de professionnels de la santé sur le capital social de la communauté francophone - Charrier, Marie-Josée (Revue du Nouvel-Ontario, 2019)

Health and healthcare utilization of Francophones in Manitoba - Chartier, Mariette; Finlayson, Gregory. S.; Prior, Heather. J.; McGowan, Kari-Lynne; Chen, Hui; de Rocquigny, Janelle; Walld, Randy; Gousseau, Michael (University of Manitoba, Manitoba Center for Health Policy, 2012)

La santé et l'utilisation des services de santé des francophones du Manitoba - Chartier, Mariette; Finlayson, Gregory. S.; Prior, Heather. J.; McGowan, Kari-Lynne; Chen, Hui; de Rocquigny, Janelle; Walld, Randy; Gousseau, Michael (University of Manitoba, Manitoba Center for Health Policy, 2012)

La pénurie de professeures de sciences infirmières au Canada et ses effets sur les programmes de formation en sciences infirmières offerts en français - Chartrand, Julie; Vandyk, Amanda; Beké, Émilie; Balasa, Rebecca; Loranger, Catherine; Muray, Mwali; Chartrand, Mariève; Baker, Cynthia (Minorités linguistiques et société, 2019)
Cette étude qualitative décrit la pénurie de professeures en sciences infirmières et ses effets actuels et potentiels sur les programmes canadiens de formation en sciences infirmières offerts en français, ainsi que les stratégies préconisées par les directrices de ces programmes afin d’en atténuer les effets. Les effets de la pénurie sont particulièrement préoccupants dans le cas des programmes offerts dans un contexte francophone minoritaire ou en région éloignée. La pénurie mettrait en péril les programmes offerts en français et menacerait, par le fait même, la qualité des services de santé offerts aux communautés francophones minoritaires au Canada. Mots-clés : pénurie professorale, sciences infirmières, professionnels de la santé, services et soins de santé en français, communautés francophones en situation minoritaire

Talk COVID to me: Language rights and canadian government responses to the pandemic - Chouinard, Stéphanie; Normand, Martin (Canadian Journal of Political Science, 2020)
Since the COVID-19 outbreak, a gradual loosening of linguistic obligations in public institutions and governments has been observed in various jurisdictions in Canada. This article argues that in addition to legal requirements to provide minority language services, it is not justifiable for governments to suspend or curtail such services in an emergency situation, for reasons pertaining to public safety and public health. After performing a survey and analysis of government actions against their constitutional, legislative, and policy language obligations to highlight best practices and deficiencies, we discuss the policy implications of these actions. In conclusion, the article considers how governments could better uphold their language obligations in times of emergency.

La discordance linguistique. L'intervenant et le patient ne parlent pas la même langue ou ne peuvent pas communiquer adéquatement [infographie] - Consortium national de formation en santé (2022)

Portrait des minorités de langue officielle au Canada : les anglophones du Québec - Corbeil, Jean-Pierre; Chavez, Brigitte; Pereira, Daniel (Statistique Canada, 2010)

Portrait of Official-Language Minorities in Canada: Anglophones in Quebec - Corbeil, Jean-Pierre; Chavez, Brigitte; Pereira, Daniel (Statistics Canada, 2010)

Les minorités prennent la parole : résultats de l'Enquête sur la vitalité des minorités de langue officielle - Corbeil, Jean-Pierre; Grenier, Claude; Lafrenière, Sylvie (Statistique Canada, 2007)

Minorities speak up: Results of the survey on the vitality ot the Official-Language Minorities - Corbeil, Jean-Pierre; Grenier, Claude; Lafrenière, Sylvie (Statistics Canada, 2007)

Portrait des minorités de langue officielle au Canada : les francophones de l'Ontario - Corbeil, Jean-Pierre; Lafrenière, Sylvie (Statistique Canada, 2010)

Portrait of Official-Language Minorities in Canada: Francophones in Ontario - Corbeil, Jean-Pierre; Lafrenière, Sylvie (Statistics Canada, 2010)

Agir ! Pour ma santé : une intervention harmonisant Services médicaux et diagnostiques et services communautaires pour les Franco-Manitobains souffrant de dépression - de Moissac, Danielle; Bohémier, Moniqu; Herdman, Chelsea; Roch-Gagné, Margaux; Paillé, Julie; Johnston, Christine; Arpin-Molinski, Michelle; Dupuis, Georgette; Saint-Hilaire, Mélanie; Prairie, Liliane (Reflets, 2012)

Impact of language barriers on quality of care and patient safety for official language minority Francophones in Canada - de Moissac, Danielle; Bowen, Sarah (Journal of Patient Experience, 2019)
Introduction: The risks to patient safety and quality of care faced by members of linguistic minority groups have been well-documented. However, little research has focused on the experience of official language minorities in Canada. Methods: This multiple method study (online and paper-based surveys combined with semi-structured individual interviews with patients and interpreters-health navigators) explored the experience of minority Francophones living in 4 Canadian provinces. Results: Patients and interpreters-navigators described experiences where language barriers contributed to poorer patient assessment, misdiagnosis and/or delayed treatment, incomplete understanding of patient condition and prescribed treatment, and impaired confidence in services received. Reliance on Google Translate and ad hoc, untrained interpreters are commonly reported, in spite of evidence highlighting the risks associated with such practice. Conclusion: Increased awareness that the risks of language barriers apply to official language minorities is essential.

Accès aux services en santé dans la langue officielle de leur choix par les minorités francophones hors Québec. Analyse de données secondaires - Diaz Pinsent Mercier Research Inc (Consortium national de formation en santé, 2021)

Préparer le terrain pour la santé en français. Rapport final - Duguay, Lise; Fortin, Pierrette; Hendriks, Edouard; Losier, Barbara; Pinet, Léo-Paul; Schofield, Aurel; St-Pierre-Ellis, Lyne; Thébeau, Marcel; Thériault, Bernadette; Vienneau, Gilles (La Société Santé et Mieux-être en français du Nouveau-Brunswick, 2007)

La recherche au profit d’un meilleur accès aux services de santé en français [numéro thématique] - Dupuis-Blanchard, Suzanne; Vézina, Sylvain (Minorités linguistiques et société / LinguisticnMinorities and Society, 2015)

Les données administratives et d’enquêtes sur l’état de santé et l’accès aux services des communautés francophones en situation minoritaire : potentiel d’analyse et état de situation. Rapport - Gaboury, Isabelle; Guignard Noël, Josée; Forgues, Éric; Bouchard, Louise (Consortium national de formation en santé, 2009)

Compétences linguistiques et qualité de services. Argumentaire pour des services de soins de santé en français de qualité - Gauthier, Hubert; Reid, Marc-André (Conseil communauté en santé en français du Manitoba, 2012)
Citation suggérée par les auteurs: GAUTHIER, Hubert et REID, Marc-André. Compétences linguistiques et qualité de services, Argumentaire pour des services de soins de santé en français de qualité, Rapport pour le compte du Conseil communauté en santé du Manitoba, déposé en mars 2012, 46 pages.

Les discours sur la santé des organismes franco-ontariens : du rapport Dubois à la cause Montfort - Gilbert, Anne; Kérisit, Michèlle; Dallaire, Christine; Coderre, Cécile; Harvey, Jean (Reflets, 2005)

Comprendre l’expérience des soins de longue durée des minorités de langue officielle au Canada : état des lieux - Hsu, Amy. T.; Ménard, Alixe; Scott, Mary (Université d'Ottawa et Institut de recherche Bruyère, 2022)
fs-ref-orig: Hsu, A. T., Ménard, A. et Scott, M. (2022). Comprendre l’expérience des soins de longue durée des minorités de langue officielle au Canada : état des lieux. Université d'Ottawa et Institut de recherche Bruyère. fs-code-orig: Hsu-2022a

Understanding the long-term care experience of official language minorities in Canada: An environmental scan - Hsu, Amy; Ménard, Alixe; Scott, Mary (Bruyère Research Institut, 2022)
fs-ref-orig: Hsu, A. T., Ménard, A., & Scott, M. (2022). Understanding the long-term care experience of official language minorities in Canada: An environmental scan. Bruyère Research Institut. fs-code-orig: Hsu-2022b

Concordance et discordance linguistique : comprendre l’expérience des patients francophones chez leur médecin de famille dans le Nord de l’Ontario - Jutras, Chloé. F. (Focus sur la recherche [Centre de recherche en santé dans les milieux ruraux et du nord], 2017)

Linguistic concordance and discordance: Understanding the Francophone patient experience during a visit to their family physicians' Office in Northern Ontario - Jutras, Chloé F. (Focus on Research [Centre for rural and northern health research], 2017)

Expérience de francophones en Ontario chez leur médecin de famille : concordance et discordance linguistique - Jutras, Chloé; Gauthier, Alain P.; Timony, Patrick E.; Côté, Daniel; Kpazaï, Georges (La Revue de la Diversité de la Recherche en Santé, 2020)
Abstract : Improving health and health care can be achieved efficiently by improving the patient experience. This study’s main objective was to capture and understand the Francophone patient experience during a visit to their family physician’s office and examining the impact of linguistic concordance or discordance on this experience. Data collection method was inspired by the first two steps of the Experience Based Design approach (EBD), six focus groups were conducted in strong French communities of Northern Ontario in which a total of twenty-nine Francophones described their experience of a visit to their family physicians’ office. The Francophone patient experience is characterized by many emotions, several of which result from the presence of linguistic concordance or discordance with the physician. Linguistic discordance in a primary care setting elicits a less favorable patient experience in terms of emotions associated with comfort, accessibility, security and personal aptitude. Actively offering French language services, being mindful of patient language preferences regardless of apparent bilingualism and providing a bilingual environment in the family physician’s office (e.g. signage, forms) would favor a positive patient experience for Francophones in Ontario.

Is Francophone language status associated with diffences in the health services use of rural Nova Scotians? - Langille, Donald; Rainham, Daniel; Kisely, Steve (Canadian Journal of Public Health, 2012)
L’étude a pour objet de vérifier empiriquement la validité d’un modèle théorique qui propose un système de relations liant la construction de l’identité ethnolinguistique à la satisfaction de vie, un aspect du mieux-être psychologique, et à l’autoévaluation de sa santé. Un échantillon de 8 124 élèves du secondaire, provenant de 30 conseils scolaires francophones situés à l’extérieur du Québec, a participé à l’étude. Les résultats sont conformes au modèle fondé sur la théorie de l’autodétermination, qui stipule que lorsque la construction identitaire se fait dans un contexte d’appui à des besoins psychologiques de base, elle est reliée au mieux-être psychologique de la personne. Abstract

Pour un système de santé en français amélioré au Nouveau-Brunswick - Leblanc, Gino (Gouvernement du Nouveau-Brunswick, 2010)

Toward an improved health system in french in New Brunswick - Leblanc, Gino (New-Brunswick Government, 2010)

L’influence de l’identité linguistique et de l’âge sur la représentation sociale des services de santé mentale chez les personnes dites dépressives - Lévesque, Maude; Negura, Lilian; Moreau, Nicolas; Laflamme-Lagoke, M. (Minorités linguistiques et société, 2018)
Cet article étudie la représentation sociale des services de santé mentale chez les personnes dites dépressives en contexte francophone minoritaire au Canada. Des entrevues semi-dirigées ont été réalisées auprès de 44 personnes s’identifiant comme francophones et anglophones. Ces dernières proviennent de Moncton, Ottawa, Sudbury et Winnipeg et ont fait l’expérience d’un épisode dépressif. L’analyse lexicographique complétée par l’analyse intégrée de contenu a fait ressortir trois grands schèmes sociocognitifs de la représentation sociale des services, qui agissent sur l’acceptabilité sociale des services de santé mentale chez les personnes francophones vivant en situation minoritaire : 1) la nature impersonnelle des compétences expertes des professionnels de la santé, 2) la facette médicale de l’identité dépressive et 3) la perte perçue du contrôle dans le contexte de soins. L’acceptabilité sociale des services de santé mentale est discutée également en fonction de la configuration de la représentation sociale des services selon l’âge. Mots-clés : minorité linguistique, francophones, santé mentale, services, dépression, représentation sociale

Les répercussions des problèmes de communication sur la prestation de soins de santé de qualité aux communautés et patients de langue minoritaire - MacLean, Patsy; Robinson, Constance; Lewis, Kay; HRA, firme d’experts-conseils (Réseau des services de santé en français de l’Île-du-Prince-Édouard et Société Santé en français, 2007)
fs-ref-orig: MacLean, P., Robinson, C. et Lewis, K. (2007). Les répercussions des problèmes de communication sur la prestation de soins de santé de qualité aux communautés et patients de langue minoritaire. Réseau des services de santé en français de l’Île-du-Prince-Édouard et Société Santé en français. fs-code-orig: MacLean-2007

Comprendre l'expérience des soins de longue durée des minorités de langue officielle au Canada : une analyse de l'environnement | Understanding the long-term care experience of official language minorities in Canada: An environmental scan - Ménard, Alixe; Scott, Mary; Hsu, Amy T. (2022)
fs-ref-orig: Ménard, A., Scott, M. et Hsu, A. T. (2022). Comprendre l'expérience des soins de longue durée des minorités de langue officielle au Canada : une analyse de l'environnement | Understanding the long-term care experience of official language minorities in Canada: An environmental scan. Institut de recherche Bruyère. fs-code-orig: Ménard-2022

Official Language Minority Communities in Ontario: Understanding the Lived Experiences of Francophone Patients and their Nursing Care Providers - Muray, Mwali (2022)
Although Canada is a bilingual country, official language minority community patients struggle to access quality care in their language. This reality has been of concern for Francophone minority communities in Ontario, but has seldom been examined in a nursing context. This research sought to examine the lived experiences of registered nurses and nursing students providing care to French-speaking patients in Ontario, as well as the realities of Francophone patients seeking French language health care services in Ontario. The conceptual frameworks guiding the study were the “Four Levels of Change for Improving Quality” model and the “Four-Level Model of the Health Care System.” Using qualitative phenomenological inquiry, as influenced by Martin Heidegger and Max van Manen, 31 semi-structured interviews were conducted with three subsets (n=10 Francophone patients; n=10 nursing students; n=11 registered nurses) throughout Ontario who had experience with the phenomenon being investigated. Data collection took place over a year (2018-2019) and was analysed thematically. Significant findings were identified across the three groups. Participants revealed the patchwork of individual actions taking place to remedy the existing gaps regarding care for Francophone minority populations. This included navigating a health care system where good enough care was the unfortunate standard for Francophone patients, and discussing how Francophone patients and nursing care providers implement strategies individually to manage the lack of resources for Francophone patient populations in Ontario. This thesis asserts that official language minority communities and their nursing care providers remain faced with difficulties providing and receiving care in Ontario. While numerous structures and resources exist to remediate the problems, these interventions and resources are not always implemented systemically, leading to a disproportionate burden on individuals, significant risks for safety for patient populations, and ethical dilemmas for nursing care providers. Recommendations are provided to bridge the gaps and ensure considerations of the needs of linguistic minorities throughout the health care system. Keywords: Francophonie, Linguistic Minorities, Nursing, Phenomenology, Qualitative Research

L'accès aux soins de santé des communautés de langue officielle en situation minoritaire (CLOSM) au Canada : une recension des écrits - Muray, Mwali; Peguero-Rodriguez, G.; Scarlett, Emilie; Perron, Amélie; Chartrand, Julie (Minorités linguistiques et société, 2022)
Cette étude présente une recension des écrits sur les expériences des patients et des prestataires de soins en ce qui concerne les services de santé au Canada offerts aux communautés de langue officielle en situation minoritaire (CLOSM). Mandatée par le Bureau d’appui aux communautés de langue officielle (BACLO), cette recension fait constat des défis et des obstacles qui entravent l’offre de services de santé et l’accès aux soins pour les CLOSM dans la langue officielle de leur choix, et propose des recommandations à l’intention des patients, des professionnels de la santé, des établissements de santé, des différents ordres de gouvernement au Canada et des chercheurs. Cette recension des écrits met en lumière le manque d’exécution systémique des stratégies, afin de faciliter l’accès aux services de santé dans leur langue pour les CLOSM fondées sur des données probantes. Elle s’interroge également sur le fait que peu de stratégies fondées sur des données probantes ont été mises en oeuvre à l’échelle du système malgré des décennies de recherche sur le sujet. Mots-clés : accès aux soins de santé, communautés de langue officielle en situation minoritaire (CLOSM), patients, professionnels de la santé, recension des écrits

Active offer of mental health and addiction services: How to serve Francophones at their most vulnerable times [oral communication] - Ontario mental health & addictions virtual care collaborative (Centre for Addiction and Mental Health (CAMH), 2021)
fs-ref-orig: Ontario mental health & addictions virtual care collaborative. (2021). Active offer of mental health and addiction services: How to serve Francophones at their most vulnerable times [oral communication]. Centre for Addiction and Mental Health (CAMH). fs-code-orig: Ontario mental health & addictions virtual care collaborative-2021

Qualité et sécurité des services de santé offerts en situation linguistique minoritaire en Ontario : investigations des données administratives de santé. - Reaume, Michael; Batista, Ricardo; Prud’homme, Denis; Tanuseputro, Peter (Minorités linguistiques et société, 2024)
Dans cet article, nous présentons une synthèse de plusieurs analyses récentes réalisées par notre groupe de recherche à partir de données administratives de santé pour mesurer la qualité et la sécurité des services de santé offerts aux francophones et allophones en Ontario, Canada. Les résultats de nos analyses démontrent que les Ontariennes et les Ontariens qui reçoivent des soins dans leur principale langue d’usage ont généralement de meilleurs résultats cliniques comparés à ceux qui reçoivent des soins dans une langue autre que leur principale langue d’usage. Ceci suggère que la qualité et la sécurité des soins offerts aux patients et aux patientes en situation de discordance linguistique pourraient être améliorées par le pairage de professionnel-patient parlant la même langue, par exemple, en référant un patient à un médecin qui parle la langue du patient, ou en s’assurant que les francophones ont accès aux services en français en milieux désignés en Ontario en vertu de la Loi sur les services en français et que les allophones puissent bénéficier de davantage de services d’interprétariat. Mots-clés : allophones, données administratives de santé, francophones, minorités de langue officielle, minorités linguistiques, qualité et sécurité des soins de santé

In-hospital patient harm across linguistic groups: A retrospective cohort study of home care recipients - Reaume, Michael; Batista, Ricardo; Talarico, Robert; Guerin, Eva; Rhodes, Emily; Carson, Sarah; Prud'homme, Denis; Tanuseputro, Peter (Journal of patient safety, 2022)
Objective Research examining the impact of language barriers on patient safety is limited. We conducted a population-based study to determine whether patients whose primary language is not English are more likely to experience harm when admitted to hospitals in Ontario, Canada. Methods We used linked administrative health records to establish a retrospective cohort of home care recipients (from 2010 to 2015) who were subsequently admitted to hospital. Patient language (obtained from home care assessments) was coded as English, French, or other. Harmful events were identified using the Hospital Harm Indicator developed by the Canadian Institute for Health Information. Results We included 190,724 patients (156,186 Anglophones, 5,110 Francophones, and 29,428 Allophones). There was no significant difference in the unadjusted risk of harm for Francophones compared with Anglophones (relative risk [RR], 0.94; 95% confidence interval [CI], 0.87–1.02). However, Allophones were more likely to experience harm when compared with Anglophones (RR, 1.14; 95% CI, 1.10–1.18). The risk of harm was even greater for Allophones with low English proficiency (RR, 1.18; 95% CI, 1.13–1.24). After adjusting for potential confounders, Anglophones and Allophones were equally likely to experience harm of any type, but Allophones more likely to experience harm from infections and procedures. Conclusions Patients whose primary language was not English or French were more likely to experience harm after admission to hospital, especially if they had low English proficiency. For these patients, the risk of harm from infections and procedures persisted in the adjusted analysis, but the overall risk of harm did not.

Patient-Physician Language Concordance and Cardiovascular Outcomes Among Patients With Hypertension. - Reaume, Michael; Labossière, Mathieu N.; Batista, Ricardo; Van Haute, Stephanie; Tangri, Navdeep; Rigatto, Claudio; Bohm, Clara; Prud’homme, Denis; Tanuseputro, Peter; Lix, L. M. (JAMA Network Open, 2025)
Importance Patients who live in minority language communities often receive health care services of lower quality and safety compared with patients who speak the majority language. Yet the outcomes associated with care provided by physicians who speak a patient’s primary language remain unknown. Objective To examine patient-physician language concordance and the risk of major adverse cardiovascular events (MACEs) among patients with hypertension. Design, Setting, and Participants This retrospective cohort study identified adults with self-reported hypertension in the Canadian Community Health Survey, a national survey that collects data from a representative sample of Canadians, from January 1, 2003, to December 31, 2014. Respondents (excluding those living in Quebec) had their hospitalization and mortality records linked to their survey responses. Data were analyzed from October 2023 to May 2024. Exposures Respondents’ primary home language was defined using language spoken most often at home. Language spoken with a regular physician was used to measure patient-physician language concordance. Respondents who spoke to their regular physician in their primary home language were classified as having received language-concordant care, while all other respondents were classified as having received language-discordant care.

Services en français dans les CLOSM : produire des données probantes pour améliorer l’accès et la qualité. Mémoire du Réseau des services de santé en français de l’Est de l’Ontario dans le cadre de la consultation sur le renouvellement du PCLOS 2013-2018 - Réseau des services de santé en français de l’Est de l’Ontario (2016)

Je suis insatisfait(e) des services de santé reçus. Que faire ? Comment procéder ? [infographie] - Réseau des services de santé en français de l'Est de l'Ontario; Santé Canada; Société Santé en français (2022)

Préparer le terrain. Soins de santé primaires en français dans le Sud de l'Ontario. Rapport régional - Réseau franco-santé du Sud de l'Ontario (2006)

Argumentaire pour la promotion d’une offre de service santé de qualité dans la langue maternelle des clients au Nunavut - Réseau Santé en français au Nunavut (2021)

Santé des francophones en milieu minoritaire. Quelle est la situation en Colombie-Britannique ? | The health of Francophone minorities. What does it mean for British Colombia? - RésoSanté Colombie-Britannique (What does it mean for British Colombia, 2021)

La recherche en santé et en services sociaux auprès des populations francophones en situation minoritaire au Canada. Revue de littérature et analyse des thèmes de recherche (2014-2016) - Sauvageau, Marie-Michèle (Association des collèges et universités de la francophonie canadienne, 2018)

Challenges faced by bilingual stroke survivors in the healthcare system: Unique considerations - Sauvé-Schenk, Katrine; Dubouloz-Wilner, Claire-Jehanne; Egan, Mary; Kristjansson, Elizabeth (Linguistic Minorities and Society, 2020)
The experiences of multilingual patients communicating with unilingual healthcare providers have been largely unexplored. The aim of this study was to investigate the experiences of bilingual stroke patients within the Canadian healthcare context. A secondary analysis was completed with data from a multiple case study of the experiences of seven, low-income bilingual Francophone stroke survivors living in a predominately English area. Data included semi-structured interviews, chart reviews and language proficiency assessments. Results demonstrated that bilingual survivors experience unique challenges, including limited French health vocabulary, use of non-standard French, and generally low health literacy levels in both languages. Participants with aphasia often used English and French interchangeably, leading to the potential for miscommunication when providers were not bilingual. The study highlights the importance of having bilingual healthcare providers when bilingual stroke survivors have communication or cognitive limitations. Keywords: Stroke, language, bilingualism, healthcare, literacy

Patient-physician language concordance and quality and safety outcomes among frail home care recipients admitted to hospital in Ontario, Canada - Seale, Emily; Reaume, Michael; Batista, Ricardo; Eddeen, Anan. Bader; Roberts, Rihannon; Rhodes, Emily; McIsaac, Daniel. I.; Kendall, Claire. E.; Sood, Manish. M.; Prud'homme, Denis; Tanuseputro, Peter (Canadian Medical Association Journal, 2022)
Background: When patients and physicians speak the same language, it may improve the quality and safety of care delivered. We sought to determine whether patient–physician language concordance is associated with in-hospital and postdischarge outcomes among home care recipients who were admitted to hospital. Methods: We conducted a population-based study of a retrospective cohort of 189 690 home care recipients who were admitted to hospital in Ontario, Canada, between 2010 and 2018. We defined patient language (obtained from home care assessments) as English (Anglophone), French (Francophone) or other (allophone). We obtained physician language from the College of Physicians and Surgeons of Ontario. We defined hospital admissions as language concordant when patients received more than 50% of their care from physicians who spoke the patients’ primary language. We identified in-hospital (adverse events, length of stay, death) and post-discharge outcomes (emergency department visits, readmissions, death within 30 days of discharge). We used regression analyses to estimate the adjusted rate of mean and the adjusted odds ratio (OR) of each outcome, stratified by patient language, to assess the impact of language-concordant care within each linguistic group. Results: Allophone patients who received language-concordant care had lower risk of adverse events (adjusted OR 0.25, 95% confidence interval [CI] 0.15–0.43) and in-hospital death (adjusted OR 0.44, 95% CI 0.29–0.66), as well as shorter stays in hospital (adjusted rate of mean 0.74, 95% CI 0.66–0.83) than allophone patients who received language-discordant care. Results were similar for Francophone patients, although the magnitude of the effect was smaller than for allophone patients. Language concordance or discordance of the hospital admission was not associated with significant differences in postdischarge outcomes.

Exploring the determinants of language barriers in health care (LBHC): Toward a research agenda for the language sciences - Segalowitz, Norman; Kehayia, Eva (The Canadian Modern Language Review, 2011)
There is growing interest in language barriers in health care (LBHC) – interest, that is, in how the quality of health care service delivery might be compromised when patients and health care providers do not share the same first language. This article discusses LBHC as an emerging research area that provides valuable opportunities for researchers in various branches of the language sciences – including, among others, applied linguistics, theoretical linguistics, psycholinguistics, second language acquisition – to conduct basic research and to make contributions to the socially important area of medical communication. This article also proposes a research agenda aimed at attracting general language researchers to the study of LBHC, an agenda that is theory driven, programmatic, problem-solving oriented, and interdisciplinary in scope. In proposing this agenda, selected examples have been reviewed from the current literature that can serve as illustrative models for how future research into LBHC can proceed.

Des soins de santé et des services sociaux sécuritaires dans sa langue. Réponse au projet de Cadre canadien sur la qualité des soins et la sécurité des patients - Société Santé en français (2019)
fs-ref-orig: Société Santé en français. (2019). Des soins de santé et des services sociaux sécuritaires dans sa langue. Réponse au projet de Cadre canadien sur la qualité des soins et la sécurité des patients. fs-code-orig: Société Santé en français-2019

Favoriser le rétablissement dans sa langue. Orientation en santé mentale en français. Version révisée - Société Santé en français (Version révisée, 2014)
fs-ref-orig: Société santé en français. (2012). Favoriser le rétablissement dans sa langue. Orientation en santé mentale en français. Version révisée. fs-code-orig: Société Santé en français-2014

Sensibilisation, structuration et consolidation en santé en français : 10 ans d’action - Société Santé en français (Reflets, 2014)

Access to psychiatrists by French-speaking patients in Ontario hospitals: 2005 to 2013 - Tempier, TempierRaymond; Bouattane, El Mostafa; Hirdes, John P. (Healthcare Management Forum, 2015)
There has been a limited amount of research suggesting that cultural and linguistic variables may affect access to health services, but no study has examined the access of French-speaking Canadians to psychiatrists. The present study used data from the Ontario Mental Health Reporting System to examine patterns of daily contact with psychiatrists in the first 3 days of admission to mental health facilities in Ontario. The results showed that after controlling for a broad range of covariates, French-speaking Ontarians were about one-third as likely to have daily contact with psychiatrists in that time period compared to English-speaking patients. These results were not explained by regional differences. Instead, they point to the possibility that language poses an important barrier to specific and highly specialized mental health services in this province.

The impact of linguistic concordance and the active offer of French language services on patient satisfaction - Timony, Patrick; Gauthier, Alain; Wenghofer, Elizabeth; Hien, Amelie (Diversity of Research in Health Journal, 2022)
Communication is essential to providing quality primary care. Linguistic concordance between patients and physicians has been linked to improved health outcomes and greater patient satisfaction. Although Canadian Francophones often struggle to access linguistics concordant health services, the concept of the active offer of French Language Services (FLS) has emerged as a means of ensuring the availability of such services and improving the francophone patient experience. However, the impact of language concordance and the active offer of FLS on patient satisfaction among Ontario Francophones remain largely unknown. Patient satisfaction surveys were collected as part of a continuing education program targeted at family physicians in Northeastern Ontario. Participating physicians distributed patient surveys consisting of select patient satisfaction questions from the Physicians Achievement Review (PAR) and select questions from the Active Offer of French Language Services in Minority Context Measure. Valid surveys were received from 235 patients. Just under half of these (44%) identified as Francophones, 62.6% had a French-speaking family physician; however, only 17.2% reported regularly speaking in French with their family physician. As hypothesized, there was a consistent tendency for Francophones who experience stronger linguistic concordance with their family physician to report higher satisfaction scores. Francophones who regularly speak French with their family physicians were more satisfied ( = 4.63) than those who rarely/never speak French ( = 4.29, F(1; 83) = 4.852; p < 0.05). There was also a statistically significant interaction between the patients' language of preference and the service language. Francophones who prefer French and regularly speak it with their family physician (linguistic concordance; adj= 4.82) were significantly more satisfied than those who prefer French yet rarely/never speak it (linguistic discordance; adj= 4.06, F(1; 75) = 11.950; p < 0.001). Furthermore, a positive correlation between patient satisfaction and the active offer was observed in Francophones (r = 0.49, p<0.001). The present findings provide evidence of the impact of linguistically adapted health care services on the satisfaction of Ontario Francophones and suggest that patient satisfaction may be improved through the active offer of FLS. A larger and more diverse sample is required to confirm these findings.

Improving access to health services in French: The power of networking and knowledge mobilization, a proven Canadian Model - Tremblay, Michel; Leis, Anne (Linguistic Minorities and Society, 2021)
Language barriers have a detrimental impact on access to health services and compromise patients’ safety. The purpose of this article is to describe and evaluate how the Société Santé en français (SSF) and the 16 French Language Health (FLH) networks used networking and knowledge mobilization for improving access to health services in French for Francophone and Acadian minority communities (FAMC). Method: Data was extracted from the 2013-2018 program’s reports and evaluation. Results confirmed that networking effectively mobilized key partners for better access to health services in French regardless of location. This access increased incrementally as a function of the customized level of support provided to the system by the SSF and the FLH networks and, to a lesser extent, when FAMC represented over 3.5% of the total population in the region, province or territory. Networking and knowledge mobilization contribute to augmenting access to safe, quality health services in French for FAMC. Keywords: access, partnership and networking, active offer, language barriers, knowledge mobilization

Étude sur les services de santé linguistiquement et culturellement adaptés : portrait pancanadien - Tremblay, Suzanne (Société Santé et Mieux-être en français du Nouveau-Brunswick, Société Santé en français et Santé Canada, 2012)

Pour des services de santé culturellement et linguistiquement adaptés - Tremblay, Suzanne (Société Santé en français et Société Santé et Mieux-être en français du Nouveau-Brunswick, 2011)
Ce document fait rapport des études : Les normes de compétences culturelles et linguistiques en santé : étude exploratoire sur les normes américaines et Étude sur les services de santé linguistiquement et culturellement adaptés : portrait pancanadien.

Study on linguistically and culturally adapted healths services: A pan-Canadian portrait - Tremblay, Suzanne (Société Santé et Mieux-être en français du Nouveau-Brunswick, Société Santé en français & Health Canada, 2012)

Vers une démarche concertée pour le renforcement de la recherche sur les langues officielles dans le secteur de la santé : bilan et pistes d’action - Vézina, Sylvain; Doiron Robichaud, Johannie (Bureau d’appui aux communautés de langue officielle de Santé Canada, 2011)
fs-ref-orig: Vézina, S. et Doiron Robichaud, J. (2011). Vers une démarche concertée pour le renforcement de la recherche sur les langues officielles dans le secteur de la santé : bilan et pistes d’action. Bureau d’appui aux communautés de langue officielle de Santé Canada. http://docplayer.fr/123792385-Vers-une-demarche-concertee-pour-le-renforcement-de-la-recherche-sur-les-langues-officielles-dans-le-secteur-de-la-sante-bilan-et-pistes-d-action.html fs-code-orig: Vézina-2011